Socio-economics of Personalized Medicine in Asia - Sun, Shirley (2017)
The second decade of the twenty-first century has witnessed a surging interest in personalized medicine with the concomitant promise to enable more precise diagnosis and treatment of disease and illness, based upon an individual's unique genetic makeup. In this book, my goal is to contribute to a growing body of literature on personalized medicine by tracing and analyzing how this field has blossomed in Asia. In so doing, I aim to illustrate how various social and economic forces shape the co-production of science and social order in global contexts. This book shows that there are inextricable transnational linkages between developing and developed countries and also provides a theoretically guided and empirically grounded understanding of the formation and usage of particular racial and ethnic human taxonomies in local, national and transnational settings.